Synthesis of Organic Ligands via Reactions of 4-Benzoyl-5-phenylamino-2,3-dihydrothiophene-2,3-dione with N-Nucleophiles - Hassan Kabirifard; Pardis Hafez Taghva; Hossein Teimouri; Niloofar Koosheshi; Parastoo Javadpour; Hanieh Bagherinejad; Soheila Seyfi; Maryam Hossein Roodbari; Elaheh Golabian (Heteroatom Chemistry)
The reaction of 4-benzoyl-5-phenylamino-2,3-dihydrothiophene-2,3-dione (1) with aminoheteroaryls, lamotrigine, 1,3-diaminoheteroaryls, dapsone, NH2R (hydroxylamine, DL-1-phenylethylamine, and metformin), and 4,4′-bipyridine in THF/H2O (1 : 1) at room temperature led to 3-N-phenylthiocarbamoyl-2-butenamides 2–5, while that with naphthylamines and 1,3-phenylenediamine in ethanol at high temperature led to 5-phenylamino-2,5-dihydrothiophene-2-ones 6–8 as organic ligands in the medium to good yields. These showed the nucleophilic attacks of N-nucleophiles, except primary aromatic amines, on thioester carboxyl group (C-2) of thiophene-2,3-dione ring 1. However, the nucleophilic attacks of primary aromatic amines on the carbonyl group (C-3) of thiophene-2,3-dione 1 occurred in the form of substituted thiophenes.